Vergil and literary theory : some late 20th century critical views on the Aeneid of Vergil with particular reference to the close of the poem - Malan, Catherina Adriana (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1993.